2018
DOI: 10.1515/tjb-2018-0113
|View full text |Cite
|
Sign up to set email alerts
|

Determination of chemical composition, antibacterial and antioxidant properties of products obtained from carob and honey locust

Abstract: Objective The objective of this study was to characterize flours and syrups, obtained from pods of carob (Ceratonia siliqua L.) and honey locust (Gleditsia triacanthos). Method Flours and syrups, produced by carob and honey locust were analyzed for moisture, ash, protein content, dietary fibers, minerals composition, total phenolic content, as well as antibacterial and antioxidant activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The sugar content is presented in Figure 2, namely sucrose, fructose and glucose. The sucrose content in undigested CF samples is of a higher quantity than the other sugars, which is in agreement with previous studies [44], and decreases and disappears after gastrointestinal digestion, which can be due to the enzymatic cleavage (amylase) and degradation of glycoside bonds, by extreme conditions such as acidity, and the inversion of sucrose into glucose and fructose units [45]. This is supported by the increase in both fructose and glucose from the oral to the gastric phase, for CF ≤ 100 µm.…”
Section: Effect Of Git Simulation On Different Particle Fractions Of ...supporting
confidence: 93%
“…The sugar content is presented in Figure 2, namely sucrose, fructose and glucose. The sucrose content in undigested CF samples is of a higher quantity than the other sugars, which is in agreement with previous studies [44], and decreases and disappears after gastrointestinal digestion, which can be due to the enzymatic cleavage (amylase) and degradation of glycoside bonds, by extreme conditions such as acidity, and the inversion of sucrose into glucose and fructose units [45]. This is supported by the increase in both fructose and glucose from the oral to the gastric phase, for CF ≤ 100 µm.…”
Section: Effect Of Git Simulation On Different Particle Fractions Of ...supporting
confidence: 93%
“…In Faro, Portugal, Carbas et al (2019) reported that commercially available carob flours had high dietary fibre levels, total phenols, D-pinitol, monosaccharides, and antioxidant activity. Another study from Turkey (Fidan et al, 2018) demonstrated that carob flour had high amounts of protein (22.56%) and dietary fibre (28.17%), being a good source of antioxidants, particularly polyphenolic compounds and minerals (Mg, Fe, and Zn). These phytochemicals have important healthy and nutritional properties that corroborate the use of carob flours as food ingredients.…”
Section: Powdermentioning
confidence: 99%
“…Whereas antimicrobial activity was not determined aganist E. coli for 100% ethanol extract, 9.44 mm zone diameter was measured in 50% ethanol extract. In a study in which flour and syrups obtained from carob (Ceratonia siliqua L.) and honey acacia (Gleditsia triacanthos) were characterized, the carob extract was shown to posses the highest antibacterial activity with inhibition zones of 22 mm against L. monocytogenes; 12 mm against E. coli, 10 mm against S. enterica and 13 mm against S. aureus (Fidan et al, 2019). Acetone and ethanol extracts of carob (Ceratonia siliqua L.) leaf and pods were evaluated for their inhibitory ability against the Gram negative Pectobacterium atrosepticum bacteria by Meziani et al (2015).…”
Section: Determination Of Antimicrobial Activitymentioning
confidence: 99%